1985
DOI: 10.1104/pp.78.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Abscisic Acid into the Apoplast in Response to Water Stress in Xanthium strumarium L.

Abstract: The effect of water stress on the redistribution of abcisic acid (ABA) in mature leaves of Xawthium strumarium L. was investigated using a pressure dehydration technique. In both turgid and stressed laves, the ABA in the xylem exudate, the 'apoplastic' ABA, icased before 'bulk leaf' stress-induced ABA accumulation began. In the initially turgid leaves, the ABA level remained constant in both the apoplast and the leaf as a whole until wilting symptoms appeared. Following turgor loss, sufficient quantities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 23 publications
5
26
1
Order By: Relevance
“…Thus, the more ABA present, whether arising from intrinsic biosynthesis or from imports, the more slowly the leaves wilted. This is consistent with the recent realization (3,9) that stress-induced ABA plays a minor role in this process: stressinduced ABA does not begin to accumulate until after initiation of stomatal closure. Furthermore, a normal phenotype was generated in the solution culture-grown mutant/wild-type plants, although the leaves retained the rapid wilting characteristic, suggesting that different plant processes require different amounts of ABA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the more ABA present, whether arising from intrinsic biosynthesis or from imports, the more slowly the leaves wilted. This is consistent with the recent realization (3,9) that stress-induced ABA plays a minor role in this process: stressinduced ABA does not begin to accumulate until after initiation of stomatal closure. Furthermore, a normal phenotype was generated in the solution culture-grown mutant/wild-type plants, although the leaves retained the rapid wilting characteristic, suggesting that different plant processes require different amounts of ABA.…”
Section: Discussionsupporting
confidence: 92%
“…The samples were then purified by semi-preparative HPLC as described (2) with some modification (3). The ABA content of the samples was quantified using a Hewlett-Packard 5840A gas chromatograph equipped with a 63Ni-electron capture detector as described (3 Endogenous ABA Levels. The endogenous ABA levels in both turgid and stressed leaflets were unaffected by the culture method under which the plants were grown (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The vp14 mutant evidently targets a pool of ABA involved in stomatal regulation in seedling leaves. Previous studies have established that stress-induced changes in bulk ABA synthesis occur too slowly to account for rapid stomatal responses in leaves and that redistribution of preexisting ABA pools can account for stomatal closure (25). It is therefore unlikely that the partial inhibition of stress-induced ABA synthesis in vp14 mutant leaves would account for the impaired stomatal regulation detected within the first 5 min after leaf excision.…”
Section: Discussionmentioning
confidence: 99%
“…Given the experimental error of the ABA measurements, the affected pool must comprise less than 20% of the basal ABA content of turgid leaves. Critical sources of ABA may include localized or very rapid synthesis of ABA in cells near the stomatal complex (25) and͞or ABA transported from the roots in the transpiration stream (26). Localized or low-level constitutive expression of Vp14 mRNA in leaf tissues is consistent with our Northern blot analysis of nonstressed leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Stomata are able to close in response to water stress signals before an increase in bulk leaf ABA is observed (e.g. Loveys, 1977;Dorffling and Tietz, 1984;Cornish and Zeevaart, 1985). These authors suggested that dehydration of detached leaves in air can release ABA sequestered in the symplast so that it accumulates in the apoplast in the vicinity of the guard cells.…”
mentioning
confidence: 99%